REALISASI DANA ALOKASI UMUM DAN PENGARUHNYA TERHADAP PERTUMBUHAN EKONOMI DAERAH RIAU PERIODE 2018-2021 - Ayu Waningsih; Arttika Rahma Sari (Adisam Publisher, 2023)
Economic growth at the regional level is a complex phenomenon influenced by various factors. The General Allocation Fund (DAU) has a central role in supporting economic development in Riau Province, which is rich in natural resources, especially oil and gas. This research aims to reveal the realization of Riau Province's DAU for the 2018-2021 period and analyze its influence on regional economic growth. The research method uses a quantitative approach with secondary data from the Riau Central Statistics Agency (BPS). Descriptive analysis, classical assumption test, t-test, and simple linear regression were used to analyze the data. The research results show that DAU realization experienced a significant decline during this period. In 2021, there will be a decrease in allocations, possibly due to the impact of the pandemic and changes in national policy. However, the results of the hypothesis test show that DAU does not have a significant effect on the economic growth of Riau Province. The conclusion of this research is that the effectiveness of DAU management needs to be re-evaluated. Although DAU provides substantial financial support, new strategies for using these funds need to be considered to achieve more optimal economic growth. These findings can be the basis for improving policies at the regional level to increase the contribution of DAU to the economic development of Riau Province.